Microsurgical Intercapsular Resection Schwannoma Without Severing Nerve Fibers: A Technique of Using Only 2 Freer Dissectors - Toshifumi Akazawa, MD; Mitsuru Sekido, MD; Yoshio Nakayama, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Schwannoma is often removed by severing the nerve fascicle of origin or microsurgical enucleation, and patients may sometimes experience postoperative neurological deficits and sensory loss. An intercapsular resection technique was devised to remove only the true tumor and preserve nerve function. We report our technique and results using only 2 Freer dissectors. Methods:. Twenty cases of schwannoma of extremities and head were treated by the same surgeon from 2018 to May 2024. The schwannoma was exposed under general anesthesia. The superficial incision was performed at an area on the epineurium where there was no funiculus, followed by total removal of the tumor using only 2 Freer dissectors without cutting nerve fibers. Results:. The patients were 12 men and 8 women with a mean age at surgery of 55 years (range: 20–81 y). The preoperative mean diameter on magnetic resonance imaging averaged 24 mm (range: 10–46 mm). The average operation time for tumor removal was 39 minutes. The average postoperative follow-up was 1 year. All patients showed improved preoperative symptoms, with no muscle weakness, movement disorders, or sensory loss. None of the cases showed residual neurological deficits or tumor recurrence. Conclusions:. This method, using 2 Freer dissectors, does not require grasping the nerve with micro forceps, and it was possible to gently strip off the surrounding normal nerve fibers from the tumor, like peeling the skin of an onion. This is an extremely useful technique that can remove only the tumor safely and in a short time without damaging nerves.